Analisis Penerapan Halal Assurance System (HAS) dalam Proses Penyembelihan Ayam: Studi Kasus pada Rumah Potong Ayam - Habibi, Ach.; Sukamto; Aslikhah (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to evaluate the implementation of the Halal Assurance System (HAS) in poultry slaughtering practices. The research focuses on assessing the conformity of the slaughtering process with HAS standards and identifying factors that influence the effectiveness of its implementation. A qualitative approach with a case study design was employed, involving data collection through observation, in-depth interviews, and documentation using triangulation techniques. Data were analyzed descriptively through the processes of reduction, presentation, and conclusion drawing. The results indicate that the implementation of HAS has been carried out in accordance with Islamic principles, including the recitation of basmalah, the orientation toward the qibla, and the cutting of the three vital channels. However, weaknesses remain in documentation, internal audit routines, and staff training. These findings highlight the importance of comprehensive halal assurance implementation to ensure compliance with Islamic law while enhancing consumer trust in animal-based products. This study is expected to contribute to the strengthening of halal governance within the poultry slaughtering industry in Indonesia.